2017
DOI: 10.17628/ecb.2017.6.49-53
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Proline-Rich Peptide-1 Protects Against Myocardial Ischemia-Reperfusion Injury

Abstract: Hypothalamic proline-rich peptide-1 (PRP-1), a neurosecretory cytokine appeared to be involved in the multiple mechanisms of cardioprotection. Dose-dependent effects of PRP-1 (4 and 8 µg) were studied in an open-chest model of myocardial ischemia-reperfusion injury (IRI). Adult male Sprague-Dawley rats underwent 40-minute left anterior descending coronary artery occlusion, under isoflurane anesthesia followed by 2 and/or 24 h of reperfusion. Groups treated with PRP-1 were compared to control. It has been revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Open-chest model of myocardial IR injury is the most acceptable and suitable model for the reproduction of human MI and screening of pharmacological activity of various compounds [56,57]. Using this model, we demonstrated that post-ischemic administration of an effective dose of PRP-1 significantly reduces in vivo necrotic area of myocardial infarction, caused by temporary occlusion of coronary artery in rats, as well as it improves cardiac hemodynamics and coronary circulation, by increasing the left ventricular ejection fraction, which is an indicator of efficiency of pumping into the systemic circulation [58].…”
Section: The Effect Of Proline-rich Peptide-1 On Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Open-chest model of myocardial IR injury is the most acceptable and suitable model for the reproduction of human MI and screening of pharmacological activity of various compounds [56,57]. Using this model, we demonstrated that post-ischemic administration of an effective dose of PRP-1 significantly reduces in vivo necrotic area of myocardial infarction, caused by temporary occlusion of coronary artery in rats, as well as it improves cardiac hemodynamics and coronary circulation, by increasing the left ventricular ejection fraction, which is an indicator of efficiency of pumping into the systemic circulation [58].…”
Section: The Effect Of Proline-rich Peptide-1 On Ischemia-reperfusion Injurymentioning
confidence: 99%